2016
DOI: 10.1016/j.homp.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric and molecular study of the apoptosis observed on tadpoles’ tail explants under the exposition of triiodothyronine in different homeopathic dilutions

Abstract: The present experiment is in agreement with the hypothesis that T3, at a 10cH homeopathic dilution, changes the metamorphosis molecular network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The expression of caspase proteins is directly related to the process of cell apoptosis. In another experiment that reproduced their previous results, Guedes et al (2016) identified lower RNA expression of caspases 3 and 7 in tadpoles stimulated by T3 solution at 100 nM and subsequently treated with the 10cH dilution of this hormone. Again, the ability of high dilutions of thyroid hormones to induce changes in the metamorphosis-related process through the water was seen.…”
Section: Resultssupporting
confidence: 80%
“…The expression of caspase proteins is directly related to the process of cell apoptosis. In another experiment that reproduced their previous results, Guedes et al (2016) identified lower RNA expression of caspases 3 and 7 in tadpoles stimulated by T3 solution at 100 nM and subsequently treated with the 10cH dilution of this hormone. Again, the ability of high dilutions of thyroid hormones to induce changes in the metamorphosis-related process through the water was seen.…”
Section: Resultssupporting
confidence: 80%